AN ENTREPRENEURIAL CREATIVE THINKING TEST FOR HIGH SCHOOL STUDENTS IN STEM EDUCATION - Sufirman Arifin; Nyet Moi Siew (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Instruments have been developed to measure entrepreneurial thinking. However, those instruments did not assess the commercial aspects of product marketing using digital technology. Consequently, the Entrepreneurial Creative Thinking Test (ECTT) was developed to assess the level of entrepreneurial creative thinking among Form Four high school students in STEM education. ECTT consists of five constructs derived from integrating the steps between the Socioscientific Issue Approach Model and the Design Thinking Process Model. The five constructs are Investigation, New Idea, Design, Create, and Commercial. The sample consisted of 187 Form Four students aged 15 to 16 years from four high schools in Sabah, Malaysia. The sample comprised 103 females (55.1%) and 84 males (44.9%). A survey research design was conducted to ascertain the extent to which the validity and reliability of this instrument can meet the psychometric characteristics of a research. The survey research design focused on the validity and reliability assessment of ten open-ended questions. This study utilised the Rasch Measurement Model to evaluate the validity and reliability of the ECTT instrument. Person fit, item fit, item polarity, unidimensionality, reliability, and item-person separation were analysed. The study’s findings revealed that the ECTT instrument has good item reliability, with a score of .97. In conclusion, the ECTT is a valid and reliable instrument for assessing the level of entrepreneurial creative thinking among Form Four students in STEM education.